The Count of Monte Cristo - Dumas, Alexandre, 1802-1870.; Bair, Lowell (New York : Bantam, 1981)
After escaping from the island where he has been in prison, Dantes plots his revenge on the people responsible for his imprisonment.
Adult
Adult.
Wilson's Senior High School
930
Keywords: France -- Fiction; France -- Fiction; Adventure fiction